Socio – Economic and Financial Efects of Kidnapping in Birnin Gwari Local Governmant Area of Kaduna State - Musa, Bushi Kasimu; Ismail, Akintola; Abdallah, Akintola (European Scientific Journal, ESJ, 2023)
This paper focuses on the socio-economic and financial effects of kidnapping in BirninGwari Local Government Area of Kaduna State, Nigeria. Structured questionnaires were used to collect data from the study area. The data obtained were analyzed using descriptive statistics and inferential statistics. Chi-square (χ2) statistic was used to test the hypothesis. This study revealed that kidnapping has a significant effect on the socio-economic activities of the study area (χ2=13.849a, α=3, p-value=0.003). To enhance the reduction in the rate of kidnapping, the government needs to provide job opportunities for the youth, train the security agencies, and provide them with the necessary equipment to fight crime, especially kidnapping, in the country. The individual community should also form an active vigilante group or any other form of informal crime control mechanism to support the effort of the police to improve the level of security in the society. There is need for improved sensitization and collaboration between the security agencies and the community and all sections of society to pass the message of safety to Nigerians on the importance of reporting suspicious behaviour to the police and other security agencies.